Collection Management and its impact on the Financial Management of the company PP S.A: Period 2014-2016 - Mogollón Gómez, Juliet (2021)
The objective is to determine the impact of collection management on the financial management of the company, taking as a reference the efficiency of the personnel who perform it, the identification of deficient processes that cause relevant internal risks and negatively impact the achievement of objectives and the implementation of collection policies to safeguard the financial resources of the company. The research design is non-experimental. With a quantitative approach, using the analysis of the company's financial statements and to verify the hypotheses, the Spearman correlation coefficient was applied. The analysis showed that there is a high correlation that has a positive impact between the main variables collection management and financial management. However, the impact of staff efficiency with respect to accounts receivable is negative because the highest percentage of this item corresponds to current debts while the remainder falls on overdue debts greater than the terms granted to clients, being a precedent for research. It was concluded that the collection management had an impact on the financial results of the company in relation to accounts receivable and their age.